C‐theories of time: On the adirectionality of time. Issue 12 (6th November 2020) - Farr, Matt
Abstract: 'The universe is expanding, not contracting'. Many statements of this form appear unambiguously true; after all, the discovery of the universe's expansion is one of the great triumphs of empirical science. However, the statement is time‐directed: the universe expands towards what we call the future; it contracts towards the past. If we deny that time has a direction, should we also deny that the universe is really expanding? This article draws together and discusses what I call 'C‐theories' of time—in short, philosophical positions that hold time lacks a direction—from different areas of the literature. I set out the various motivations, aims and problems for C‐theories, and outline different versions of antirealism about the direction of time.